2020
DOI: 10.1002/lpor.202000029
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Transport and Intervalley Scattering Dynamics in Large‐Size Exfoliated MoSe2 Monolayer Investigated by Heterodyned Transient Grating Spectroscopy

Abstract: Exciton intervalley scattering, annihilation, relaxation dynamics, and diffusive transport in monolayer transition metal dichalcogenides are central to the functionality of devices based on them. Here, these properties in a large-size exfoliated high-quality monolayer MoSe 2 are addressed directly using heterodyned transient grating spectroscopy at room temperature. While the free exciton population is found to be long-lived (≈230 ps), an extremely fast intervalley scattering (≤170 fs) is observed, leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 95 publications
2
12
0
Order By: Relevance
“…The sub-100 fs fluence-independent intervalley coupling in our work is therefore likely distinct from this exchange-mediated or other exciton scattering mechanisms. Kuhn et al observed fluence-independent ∼170 fs intervalley depolarization (equal to the autocorrelation width of their 120 fs pulse) in monolayer MoSe 2 , consistent with Rashba-induced mixing of dark and bright exciton states . However, this coupling is predicted to be negligible in MoS 2 and is therefore likely not responsible for the observed coupling features in our experiments.…”
Section: Resultssupporting
confidence: 83%
“…The sub-100 fs fluence-independent intervalley coupling in our work is therefore likely distinct from this exchange-mediated or other exciton scattering mechanisms. Kuhn et al observed fluence-independent ∼170 fs intervalley depolarization (equal to the autocorrelation width of their 120 fs pulse) in monolayer MoSe 2 , consistent with Rashba-induced mixing of dark and bright exciton states . However, this coupling is predicted to be negligible in MoS 2 and is therefore likely not responsible for the observed coupling features in our experiments.…”
Section: Resultssupporting
confidence: 83%
“…[ 61,144,173 ] At higher generation rates, the PL QY of MoS 2 (and other TMDCs) drops as recombination at high exciton densities is dominated by the annihilation of two adjacent excitons, a process so‐called exciton–exciton annihilation (EEA). [ 99,217–220 ] EEA is a process in which neutral excitons recombine nonradiatively in the course of colliding with other excitons, causing a reduction in the luminescent efficiency of the material at higher generation rates. [ 99,217–220 ] To eliminate the efficiency droop in 2D semiconductors, a detailed investigation on the origin of the EEA process is required.…”
Section: Strategies To Enhance the Brightness Of Monolayer Tmdcsmentioning
confidence: 99%
“…[ 99,217–220 ] EEA is a process in which neutral excitons recombine nonradiatively in the course of colliding with other excitons, causing a reduction in the luminescent efficiency of the material at higher generation rates. [ 99,217–220 ] To eliminate the efficiency droop in 2D semiconductors, a detailed investigation on the origin of the EEA process is required. It is found that the lifetime of excitons is inversely related to the EEA coefficient ( C EAA ), a parameter that measures the rate of annihilation.…”
Section: Strategies To Enhance the Brightness Of Monolayer Tmdcsmentioning
confidence: 99%
“…Transient grating based approaches have been extensively used for the measurement of the diffusion properties of charge carriers. Among the successful examples are applications to studying exciton diffusion [16] and, more recently, 2D materials such as WSe 2 [25] and MoSe 2 [26] monolayers. Another example are ambipolar mobilities, e.g., the combined electron and hole mobility, in semiconductors [27][28][29] including the recent observation of high ambipolar mobility and ultra-high thermal conductivity in cubic boron arsenide [30] by the Chen group, a finding that was in parallel reported by Yue et al, using widefield imaging-based transient reflection SPTM: [31] This is a great example of how compatible information can be obtained using different SPTM techniques.…”
Section: "Normal" Diffusion Of (Quasi)particlesmentioning
confidence: 99%
“…More recently, the same approach was used to study rapid valley depolarization in 2D materials, occurring within 170 femtoseconds for MoSe 2 . [26,34] Point-scanning SPTM has been used to study the (quasi-) particle transport in a host of different materials. Earlier work focused on nanowires, from ensembles of carbon nanotubes, [35] to experiments resolving single nanowires of gold [36] and silicon, [37] to more complex systems and geometries, such as p-i-n junction nanowires, [38] as well as suspended nanowires.…”
Section: "Normal" Diffusion Of (Quasi)particlesmentioning
confidence: 99%